Réponses

Meilleure réponse !
2014-04-29T13:04:56+02:00
1) A = (x - 6)² - (x - 4) (x - 9)
A = (x - 6)² + (-x + 4) (x - 9)
A = x² - 12x + 36 - x² + 9x + 4x - 36
A = x² - x² - 12x + 9x + 4x + 36 - 36
A = -12x + 9x + 4x
A = x

2) 9 994² - 9 996 × 9 991 = (10 000 - 6)² - (10 000 - 4) (10 000 - 9)
Avec x = 10 000 d'après la question 1 : 9 994² - 9 996 × 9 991 = 10 000

3) 124 124 124 118² - 124 124 124 120 × 124 124 124 115 
 = (124 124 124 124 - 6)² - (124 124 124 124 - 4) (124 124 124 124 - 9)
Avec x = 124 124 124 124 d'après la question 1 : 124 124 124 118² - 124 124 124 120 × 124 124 124 115 = 124 124 124 124